1988
DOI: 10.1111/j.1365-2362.1988.tb01161.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sodium valproate on haem biosynthesis in man: implications for seizure management in the porphyric patient

Abstract: The short-term effects of sodium valproate (VPA) on haem biosynthesis were assessed in a placebo-controlled crossover trial in eight healthy male subjects who ingested VPA 500 mg t.i.d. and matched placebo for 5 days. All showed augmented activity of leucocyte 5-aminolaevulinate synthase (ALA-S) activity, the rate-limiting enzyme of the haem biosynthetic pathway, following 3 and 5 days of VPA treatment (P less than 0.001). This was accompanied by increased urinary excretion of 5-aminolaevulinic acid (ALA; P le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The unsaturated metabolite of valproic acid is chemically related to AIA (Baillie, 1988). Not surprisingly, valproic acid has been documented to be porphyrogenic in human (McGuire et al, 1988). Compound 1 might undergo the same two parallel reactions, ␤-hydroxylation to compound 3 and desaturation of the butyramide (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The unsaturated metabolite of valproic acid is chemically related to AIA (Baillie, 1988). Not surprisingly, valproic acid has been documented to be porphyrogenic in human (McGuire et al, 1988). Compound 1 might undergo the same two parallel reactions, ␤-hydroxylation to compound 3 and desaturation of the butyramide (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…19 Whereas some AEDs are known to exacerbate porphyric attacks, others are thought to be safe for porphyria, controlling seizures without exacerbating the attacks. [21][22][23][24][25][26][27][28][29][30][31][32][33] Five of our patients were treated with GBP, two of them for neuropathic pain (8, 9, and 11). Pain was reported to be improved to some extent in two of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that carbamazepine reduces PBG deaminase activity (Rapeport et al, 1984) but it has subsequently been appreciated that it is the activity of ALA dehydratase that is reduced by this drug (McGuire et al, 1988a (McGuire et al, 1988b) and yet interestingly PBG deaminase activity in both patients rose on discontinuing valproate (Figure 1 (Rapeport et al, 1984;McColl et al, 1980). Sodium valproate, although not an enzyme inducer, stimulates porphyrin production in normal individuals by mechanisms as yet unclear (McGuire et al, 1988b). As PBG deaminase is a secondary ratecontrolling step in haem biosynthesis (Brodie et al, 1977b), marked induction of the primary rate-controlling enzyme ALA synthase could result in accumulation of porphyrin precursors similar to that occurring in AIP.…”
Section: Discussionmentioning
confidence: 99%